Analisis Evaluasi Kinerja PDAM Tirta Jeneberang di Kabupaten Gowa Berdasarkan Balance Scorecard - Edward Panji Rachman; Sumardi Sumardi; Musran Munizu (Hasanuddin Journal of Business Strategy, 2019)
In its development from 2016-2017, the number of healthy PDAMs always increased, while PDAMs were less healthy and sickness experienced fluctuations. The purpose of this study was to determine the performance of PDAM Tirta Jeneberang Gowa Regency on a financial perspective, customer perspective, internal business process perspective, and growth and learning perspective and evaluate the results of performance appraisal and make suggestions for future improvements in order to improve service to the community and its contribution to the Regional Government of Gowa Regency. Research on the performance of PDAM Tirta Jeneberang in Gowa district based on balance scorecard is a descriptive research type. The results of the study show that the financial perspective measures the company's financial performance, showing the contribution of the company's strategy to increase profits and the financial performance of PDAM Tirta Jeneberang has not shown optimization as billing effectiveness is still lacking Customer perspective measures the company's service performance to meet and satisfy customer needs. The internal growth perspective still leaves a number of problems, including the level of water loss still around 30 percent and cannot be minimized and the rate of change in the water meter of the customer of PDAM Tirta Jeneberang, Gowa Regency continues to increase. The learning perspective and the growth of HR, in general, have been able to give satisfaction to employees